(untitled) (Journal of the College of Basic Education, 2023)
In this study, three different kinds of fibers (palms, Coconut, Tamarind) were tested at the room temperature. The sorbent dosage was studied in batch experiments. The experiments were carried out with (0.1-0.25)g of fibers in 25ml synthetic waste water containing about 4ppm Lead ions. Experiments showed that this topic all material have the ability to adsorption but differentiated palms fiber with (99.5%) removal efficiency , Coconut fiber with (97.5%) , and Tamarhind fiber with (97%).